Kredibilitas Komunikator Jurus Sehat Rasulullah di Kalangan Followers Instagram @Zaidulakbar (Communication Credibility of the Healthy Way of the Prophet on Instagram Followers @Zaidulakbar) - R. Yogie Prawira W.; Hindina Maulida (Jurnal Dakwah Risalah, 2020)
This study aims to determine the correlation of the source credibility with the attitudes of Instagram account followers @zaidulakbar regarding the healthy style of Rasulullah (JSR). The method used in research is a quantitative method, with correlational studies aimed at expressing relationships between variables through correlational statistics. The sampling technique used was simple random sampling with a total sample of 100 followers. Research data was collected by distributing questionnaires containing structured questions and disseminated via the direct message (DM) feature on Instagram. The data obtained were analyzed using descriptive data analysis techniques and inferential statistical analysis with the Spearman Rank statistical calculation formula (Rs). The results showed that there is a high correlation between the source credibility with the attitude of Instagram account followers @zaidulakbar of 0.834. The source credibility component consists of expertise, trustworthiness, and attractiveness.